Cellulose Nanofibers from Palm Bio-waste as Separator Membrane for EDLC - Jamaluddin, K.A. (Springer Science and Business Media B.V., 2021)
Empty fruit bunch (EFB) is a kind of bio-waste formed during the production process of palm oil. EFB is what remains of the fresh fruits bunch after the fruit has been removed for oil pressing. Therefore, this bio-waste was suggested for developing separator as the electronic component for electric double layer capacitor (EDLC). Separator made from paper pulp causes deforestation contributing more carbon dioxide building up in the atmosphere. Hence, bio-waste could possibly alternative to existing material for the separator. The objectives of this study are to prepare separators (microfiber and nanofiber) from EFB and characterize it in terms of morphology, surface area, porosity, and ionic conductance. The fibers were prepared from bio-waste through laboratory synthesis. The preparation of EFB into a cellulose microfiber and nanofiber covers; washing process, alkaline treatment and digestion, grinding, bleaching, dissolution, and electrospinning. The characterization and performance test such as morphology, ionic conductivity, surface area and porosity was performed. This project successfully produced cellulose microfiber membrane (separator) made from 100 EFB and cellulose nanofiber membrane (separator) by electrospinning technique. The measured cellulose microfiber diameter was found to be 7Â Î¼m. The ionic conductivity of microfiber separator was measured to have 1.600 Ã 10â3Â SÂ cmâ1 while the surface area and porosity tends to have the value of 1.638Â m2/g and 48.73. The diameter of cellulose nanofiber from EFB was found to be 42Â nm. The measured ionic conductivity indicated the value was 1.552 Ã 10â3Â SÂ cmâ1 where the value of surface area and porosity were 7.298Â m2/g and 51.15, respectively. Â© 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.